Pertanggungjawaban Pidana Pelaku Deepfake Porn Berbasis Artificial Intelligence di Indonesia dan Korea Selatan - Ajeng Putri Berliana; Murry Darmoko Moersidin (DE RECHT (Journal of Police and Law Enforcement), 2026)
The rapid advancement of Artificial Intelligence (AI) brings both benefits and challenges. While AI offers significant ease in various aspects of human life, it also contributes to the emergence of new crimes, such as identity forgery for illegal gain through Deepfake technology. The increasing sophistication of Deepfakes has raised serious concerns, especially with their misuse in the form of Deepfake Pornography. This phenomenon poses a growing threat to social media users and has drawn widespread public and governmental attention. This research employs a normative legal approach, focusing on statutory regulations and relevant legal doctrines. The study compares legal responses to Deepfake Pornography in Indonesia and South Korea. In Indonesia, there is no specific law addressing Deepfake Pornography; thus, existing laws such as Law No. 11 of 2008 on Electronic Information and Transactions, Law No. 44 of 2008 on Pornography, and Law No. 12 of 2022 are applied. Conversely, South Korea addresses this issue through the Criminal Law Act No. 20908 of 2025 and the Sexual Violence Punishment Act No. 20459. The study finds that both countries have made efforts to respond to the threat of Deepfake Pornography, yet each legal system has its own strengths and weaknesses. This comparative analysis aims to provide insight into the effectiveness of current legal frameworks and to contribute to the development of more comprehensive and responsive regulations.